PERANCANGAN MEJA LAPTOP ERGONOMIS DI MASA PANDEMI COVID-19 DENGAN PENDEKATAN ANTROPOMETRI DAN METODE QUALITY FUNCTION DEPLOYMENT (QFD) - Tina Hernawati Suryatman; Resti Linayah (Jurnal Teknik, 2021)
During the COVID-19 pandemic, many patterns of change in activities that were once normal have turned into virtual activities. One of them is the work from home system experienced by workers and the online learning system that occurs among students. Behind virtual activities like this, of course, they have to do long activities by staring at the laptop screen and need a laptop table to support this virtual activity. The use of inappropriate and non-ergonomic desks when working or studying from home can cause fatigue (fatigue) in some of the user's skeletal muscles. This research was conducted in order to be an innovative initiative and idea for the design of an ergonomic table design, functionality according to the needs and desires of its users, especially during a pandemic as it is today with its method approach, namely QFD and anthropometric suitability. The process of collecting data using a questionnaire, analyzing the data by determining percentiles, testing the validity, reliability, adequacy and uniformity of the data, then processed by HOQ analysis. The design of the resulting table product is a table with a design that can reduce musculoskeletal complaints, can be used for a sitting position or on a chair. The dimensions of this table are 70 cm long, 44 cm wide, 39 cm high when used on a bench and 68 cm maximum when sitting on a chair. In addition, this table also has additional features for drinking water insulation, book storage drawers, cooling pad holes, charger sockets and the table is easy to move because the table legs have wheels